2018
DOI: 10.1101/280503
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electron cryo-microscopy structure of the canonical TRPC4 ion channel

Abstract: Canonical transient receptor channels (TRPC) are non-selective cation channels. They are involved in receptor-operated Ca 2+ signaling and have been proposed to act as store-operated channels (SOC). Their malfunction is related to cardiomyopathies and their modulation by small molecules has been shown to be effective against renal cancer cells. The molecular mechanism underlying the complex activation and regulation is poorly understood. Here, we report the electron cryo-microscopy structure of zebrafish TRPC4… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 72 publications
4
50
0
1
Order By: Relevance
“…In the past few years, the resolution revolution in cryo‐electron microscopy brought several high‐resolution structures of TRP channels. Recently, two different groups solved the electron cryo‐microscopy structure of the TRPC4 ion channel (Duan et al, ; Vinayagam et al, ). Vinayagam et al () reported a structure of mouse TRPC4 in its apo state to an overall resolution of 3.3 Å.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past few years, the resolution revolution in cryo‐electron microscopy brought several high‐resolution structures of TRP channels. Recently, two different groups solved the electron cryo‐microscopy structure of the TRPC4 ion channel (Duan et al, ; Vinayagam et al, ). Vinayagam et al () reported a structure of mouse TRPC4 in its apo state to an overall resolution of 3.3 Å.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recently, two different groups solved the electron cryo‐microscopy structure of the TRPC4 ion channel (Duan et al, ; Vinayagam et al, ). Vinayagam et al () reported a structure of mouse TRPC4 in its apo state to an overall resolution of 3.3 Å. The comparison of the mouse TRPC4 structure with other TRP channel structures solved earlier (human TRPM4, mouse TRPV1, human TRPA1, human TRPP1, and mouse TRP mucolipin 1) revealed similarities as expected (Duan et al, ).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several high resolution TRPC structures have been determined by single-particle cryo-electron microscopy (cryo-EM), including zebrafish TRPC4, 32 mouse TRPC4, 33 and mouse TRPC5. 34 To date, TRPC6 is the only TRPC channel for which small molecule-bound structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The regions with the largest structural divergences are the intracellular domains. While TRPV channels are almost structurally identical [3,[5][6][7][8][9][10][11] and share homology with TRPA1 [12], the TRPM and TRPC channels have amino and carboxy-termini with very different topology [13][14][15][16][17][18][19] (Figure 1). The thermoTRP channels are a subgroup of 11 members of the TRPA, TRPV, TRPC, and TRPM subfamilies.…”
Section: Introductionmentioning
confidence: 99%